In silico evaluation of DNA Damage Inducible Transcript 4 gene (DDIT4) as prognostic biomarker in several malignancies - Joseph A. Pinto (Nature Portfolio, 2017)
Abstract DDIT4 gene encodes a protein whose main action is to inhibit mTOR under stress conditions whilst several in vitro studies indicate that its expression favors cancer progression. We have previously described that DDIT4 expression is an independent prognostic factor for tripe negative breast cancer resistant to neoadjuvant chemotherapy. We herein report that high DDIT4 expression is related to the outcome (recurrence-free survival, time to progression and overall survival) in several cancer types. We performed in silico analysis in online platforms, in pooled datasets from KM Plotter and meta-analysis of individual datasets from SurvExpress. High levels of DDIT4 were significantly associated with a worse prognosis in acute myeloid leukemia, breast cancer, glioblastoma multiforme, colon, skin and lung cancer. Conversely, a high DDIT4 expression was associated with an improved prognostic in gastric cancer. DDIT4 was not associated with the outcome of ovarian cancers. Analysis with data from the Cell Miner Tool in 60 cancer cell lines indicated that although rapamycin activity was correlated with levels of MTOR, it is not influenced by DDIT4 expression. In summary, DDIT4 might serve as a novel prognostic biomarker in several malignancies. DDIT4 activity could be responsible for resistance to mTOR inhibitors and is a potential candidate for the development of targeted therapy.